2022
DOI: 10.3390/ijerph192113989
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Coagglomeration, Green Innovation, and Manufacturing Carbon Emissions: Coagglomeration’s Dynamic Evolution Perspective

Abstract: The achievement of China’s low-carbon development and carbon neutrality depends heavily on the decrease of manufacturing carbon emissions. From coagglomeration’s dynamic evolution perspective, by using panel-threshold-STIRPAT and mediation-STIRPAT models, this study examines the relationships among industrial coagglomeration, green innovation, and manufacturing carbon emissions and explores the direct and indirect function mechanisms. Panel data of China’s 30 provinces from 2010 to 2019 are employed. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…This empirical result reflects the positive impact on carbon productivity despite the significant differences in the degree of ICT industrial co-agglomeration across regions. It has similarities with the findings of Zhang et al [71] They concluded that for 90% of the regions in China, industrial co-agglomeration is beneficial in reducing carbon emissions from manufacturing. In contrast to the findings of this paper, Wang et al [72] concluded that there are regional differences in the impact of the digital economy on low-carbon, sustainable urban development.…”
Section: Results Of Gtwrsupporting
confidence: 87%
“…This empirical result reflects the positive impact on carbon productivity despite the significant differences in the degree of ICT industrial co-agglomeration across regions. It has similarities with the findings of Zhang et al [71] They concluded that for 90% of the regions in China, industrial co-agglomeration is beneficial in reducing carbon emissions from manufacturing. In contrast to the findings of this paper, Wang et al [72] concluded that there are regional differences in the impact of the digital economy on low-carbon, sustainable urban development.…”
Section: Results Of Gtwrsupporting
confidence: 87%
“…Control variables. Since there are many external factors affecting industrial green transformation [ 44 , 45 , 46 , 47 , 48 ], eight external factors are selected as control variables in this study to minimize the interference of confounding variables on causal effect estimation and obtain more accurate fitting results. Industry density (ID): measured using the ratio of the secondary and tertiary industries’ added value to the urban built-up zone exemption.…”
Section: Methodsmentioning
confidence: 99%
“…The "innovation compensation" effect can not only partially or completely offset the additional costs incurred by enterprises in complying with environmental regulations, but also enables enterprises to gain a market-competitive advantage [62]. In addition, GTI can facilitate the low-carbon transformation of RBCs through energy-saving innovations in the pollution generation stage, terminal treatment of pollution emissions and improvement of resource and energy utilization efficiency [63]. Driven by "carbon emission reduction targets," the government has generally adopted continuous and rigorous environmental regulations.…”
Section: Hypothesis 1 (H1) Environmental Regulations Can Facilitate A...mentioning
confidence: 99%